PENGARUH PEMBERIAN REBUSAN DAUN ALPUKAT UNTUK PENURUNAN TEKANAN DARAH PADA LANSIA PENDERITA HIPERTENSI DI DESA BUARAN MANGGA KECAMATAN PAKUHAJI - Astuti, Yuyun; Depeda, Andre; Sari, Rina Puspita (Nusantara Hasana Berdikari, 2022)
Hypertension has symptoms such as headaches, fatigue, shortness of breath, and anxiety, for the management of hypertension are pharmacological and non-pharmacological, for non-pharmacological use avocado leaf decoction which contains flavonoids that can lower blood pressure. The purpose of this study was to determine the effect of boiled avocado leaves on the elderly with hypertension. Research Methods: a mixed method approach with descriptive analytic population in this study were the elderly in Buaran Mangga Village, Pakuhaji District as many as 64 respondents, researchers took about 20 respondents. The instruments used were interview sheets, sphygmomanometer and stethoscope and intervention. The results of the study analysis of blood pressure data, the average values ​​were: systolic pretest 147.25% and diastolic 99.75%, while the posttest experienced a decrease in the average value, namely systolic 139.25 and diastolic 94.75%. And the results of interviews that researchers have conducted with elderly respondents often complain of headaches, dizziness, and after drinking avocado leaf stew for several days, they feel fresh and healthy and there are no complaints or side effects from the avocado leaf stew.